2019
DOI: 10.12688/wellcomeopenres.15066.2
|View full text |Cite
|
Sign up to set email alerts
|

Spo13 prevents premature cohesin cleavage during meiosis

Abstract: Background: Meiosis produces gametes through two successive nuclear divisions, meiosis I and meiosis II. In contrast to mitosis and meiosis II, where sister chromatids are segregated, during meiosis I, homologous chromosomes are segregated. This requires the monopolar attachment of sister kinetochores and the loss of cohesion from chromosome arms, but not centromeres, during meiosis I. The establishment of both sister kinetochore mono-orientation and cohesion protection rely on the budding yeast meiosis I-spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 73 publications
(126 reference statements)
1
4
0
Order By: Relevance
“…However, ChIP-qPCR revealed that both Sgo1 and Spo13 localize to chromosomes in eco1- aa cells ( Figure 8—figure supplement 2 ). Both proteins follow a similar pattern to Rec8, showing reduced chromosomal association in eco1-aa cells that is rescued by WPL1 deletion ( Figure 8—figure supplement 2 ), consistent with a requirement for cohesin for the chromosomal association of Sgo1 and Spo13 ( Galander et al, 2019b ; Kiburz et al, 2005 ). Therefore, a failure in cohesin protection is unlikely to be the cause of meiosis II missegregation in eco1-aa cells.…”
Section: Resultssupporting
confidence: 53%
See 2 more Smart Citations
“…However, ChIP-qPCR revealed that both Sgo1 and Spo13 localize to chromosomes in eco1- aa cells ( Figure 8—figure supplement 2 ). Both proteins follow a similar pattern to Rec8, showing reduced chromosomal association in eco1-aa cells that is rescued by WPL1 deletion ( Figure 8—figure supplement 2 ), consistent with a requirement for cohesin for the chromosomal association of Sgo1 and Spo13 ( Galander et al, 2019b ; Kiburz et al, 2005 ). Therefore, a failure in cohesin protection is unlikely to be the cause of meiosis II missegregation in eco1-aa cells.…”
Section: Resultssupporting
confidence: 53%
“…Therefore, Eco1 is essential for chromosome segregation during meiosis II, even in the absence of Wpl1. One potential explanation for these findings is that localization of the cohesin protector protein, shugoshin (Sgo1), or the meiotic protein Spo13, which is also required for cohesin protection during meiosis I ( Galander et al, 2019b ; Galander et al, 2019a ; Katis et al, 2004 ; Lee et al, 2004 ), may require Smc3 acetylation. However, ChIP-qPCR revealed that both Sgo1 and Spo13 localize to chromosomes in eco1- aa cells ( Figure 8—figure supplement 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with this possibility, it has been shown that overexpression of CDC5 from the CUP1 promoter during meiosis leads to reduced electrophoretic mobility and premature degradation of Spo13 [48]. Spo13 is a critical regulator of centromeric cohesion and it is required for proper chromosome segregation at meiosis I [49]; in fact, SPO13deficient cells undergo a single round of meiotic nuclear division and generate dyads [50]. The reduced spore viability and impaired formation of asci containing 4 spores observed in the cdc5-ΔN70 mutant (Figure 3) may be a consequence of altered Spo13 and/or cohesin function.…”
Section: Discussionmentioning
confidence: 94%
“…However, there is evidence that links the development of aneuploidies to advanced maternal age: recombination errors that occur during the fetal development of the mother, age-related accumulation of damaged DNA, cohesin degradation during dictyate that can lead to the premature loss of chromosomes or sister chromatids ( Duncan et al ., 2012 ) and alterations in the SAC during the spindle formation process, inevitably leading to the delay of cell division ( Hauf & Watanabe, 2004 ; Tanaka, 2005 ; Touati & Wassmann, 2016 ). A weakened SAC would lead to the premature onset of anaphase prior to chromosomal attachment to the spindle microtubules, thus leading to potential errors in chromosome segregation ( Galander et al ., 2019 ). Likewise, it has been demonstrated that aging also has a negative effect in the concentration of cohesion and inhibin proteins, which are part of the SAC, and play a key role in normal cell division patterns ( Duncan et al ., 2012 ; Nabti et al ., 2017 ).…”
Section: Maternal Effect On Trisomy 21mentioning
confidence: 99%